Human Target Proteins for Benzo(a)pyrene and Acetaminophen (And Its Metabolites): Insights from Inverse Molecular Docking and Molecular Dynamics Simulations - Yina Montero-Pérez; Nerlis Pájaro-Castro; Nadia Coronado-Posada; Maicol Ahumedo-Monterrosa; Jesus Olivero-Verbel (Scientia Pharmaceutica)
Acetaminophen (APAP) is a widely used analgesic and antipyretic, whereas benzo(a)pyrene (B[a]P) is a carcinogen with significant global health risks due to environmental exposure. While APAP is generally safe at therapeutic doses, co-exposure to B[a]P can exacerbate its toxicity. This study aimed to identify potential human target proteins for B[a]P and APAP through inverse molecular docking and molecular dynamics simulations. We performed inverse docking with B[a]P, APAP, and three APAP metabolites against 689 human proteins involved in various biological processes. Five proteins were selected based on high docking affinity and their involvement in multiple pathways. Molecular dynamics simulations revealed that B[a]P primarily interacted via hydrophobic and π-stacking interactions with proteins like LXR-β, HSP90α, HSP90β, and AKT1, while AM404 formed hydrogen bonds and hydrophobic interactions. The simulations confirmed that the complexes had high conformational stability, except for protein AKT1. These results provide insights into the potential impacts of B[a]P and AM404 on protein functions and their implications for understanding the toxic effects of combined exposure.